2015
DOI: 10.1080/21645515.2015.1076599
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of influenza vaccine among HIV-infected adults: Conventional vaccine vs. intradermal vaccine

Abstract: Several studies have reported poor immune responses to conventional influenza vaccines in HIV-infected individuals. This study sought to elicit more potent immunogenicity in HIV-infected adults using an intradermal vaccine compared with a conventional intramuscular vaccine. This multicenter, randomized, controlled, open-label study was conducted at 3 university hospitals during the 2011/2012 pre-influenza season. Three vaccines were used in HIV-infected adults aged 18 - 60 years: an inactivated intramuscular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Many national health authorities recommend immunisation of HIV+ individuals against influenza due to potential for increased susceptibility and/or disease severity 19 . Conventional or adjuvanted influenza vaccines are immunogenic in HIV+ adults 20 21 22 23 and children 24 25 26 27 , however the induction and maintenance of influenza-specific antibody titres is frequently lower than in comparable HIV− controls, particularly in the absence of ART or in infected subjects with low CD4 T cell counts 24 26 28 29 30 31 . Similarly, the establishment of influenza vaccine-elicited memory B cell responses, as measured by polyclonal stimulation and B cell ELISpot, are diminished compared to healthy controls 12 .…”
mentioning
confidence: 99%
“…Many national health authorities recommend immunisation of HIV+ individuals against influenza due to potential for increased susceptibility and/or disease severity 19 . Conventional or adjuvanted influenza vaccines are immunogenic in HIV+ adults 20 21 22 23 and children 24 25 26 27 , however the induction and maintenance of influenza-specific antibody titres is frequently lower than in comparable HIV− controls, particularly in the absence of ART or in infected subjects with low CD4 T cell counts 24 26 28 29 30 31 . Similarly, the establishment of influenza vaccine-elicited memory B cell responses, as measured by polyclonal stimulation and B cell ELISpot, are diminished compared to healthy controls 12 .…”
mentioning
confidence: 99%
“…Among the included studies (n = 51) [ [39] , [89] ], 19 studies compared ID immunisation to SC immunisation of which all, except one [ 87 ], were historic studies (1949–1981) [ 42 , 44 , 45 , 52 , 53 , 57 , 58 , 61 , 64 , [66] , [67] , [68] , [69] , [70] , 72 , 73 , 77 , 89 ]. Studies comparing IM immunisation with ID (n = 32) immunisation were conducted more recently and were all published after 2003 [ [39] , [40] , [41] , [46] , [47] , [48] , [49] , [50] , [51] , [54] , [55] , [56] , 59 , 60 , 62 , 63 , 65 , 71 , [74] , [75] , [76] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , 88 ], with the exception of Brown et al [ 43 ] published in 1977. Study populations of the identified studies on influenza vaccines consisted of healthy adults, elderly, children (0–18 years), chronically ill and immunocompromised patients, or combinations of these groups.…”
Section: Resultsmentioning
confidence: 99%
“…Study populations of the identified studies on influenza vaccines consisted of healthy adults, elderly, children (0–18 years), chronically ill and immunocompromised patients, or combinations of these groups. Many (n = 19) studies did not report whether participants were immunised in the last six months with influenza vaccine [ 42 , 43 , 48 , 51 , 57 , 59 , 62 , 64 , 66 , 68 , 69 , 71 , 75 , 81 , 82 , 84 , 86 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a more recent, smaller study of HIV-infected children and young adults did not show improved antibody responses with high-dose vaccination [ 40 ]. Intradermal vaccines have been studied, and although they allow for the use of smaller antigenic doses, they do not appear to elicit greater immune responses and may be associated with more local and systemic side effects [ 41 , 42 ]. Finally, the use of adjuvanted vaccines (e.g., with AS03 ® or MF59 ® adjuvants) have generally produced greater immune responses post-vaccination [ 38 , 43 45 ].…”
Section: Inactivated Vaccines With Overall Broad Indicationsmentioning
confidence: 99%